Using ketofol (a mixture of ketamine and Propofol ) during Laparoscopic cholecyctectomy with local anesthesia (Latakia University Journal -Medical Sciences Series, 2024)
Introduction:The term "Hypnosedation" defines a state of minor medicinal sedationaccompanied by Hypnosis. This technique has been used in local anaesthesia proceduresA few studies have employed the concept of this case study/paper in exploring the possibility of performing laparoscopic surgery under local anaesthesia in addition to sedation. In addition to other studies that highlight the efficacy and safety of the use of Ketofol (a mixture of ketamine and Propofol) as sedative during diagnostic endoscopic procedures ( gastroendoscopy, bronchoscopy .. ) and other minor ambulatory procedures.Significance:This study demonstrates, in a practical manner, the possibility of the use of Ketofol along with local anaesthesia in laparoscopic cholecystectomy (note that Ketofol is a safe and effective combination of Ketamine and Propofol).Purpose of the study:Examine the possibility of performing laparoscopic cholecystectomy using Ketofol in order to reduce the risks accompanied by general anaesthesia and endotracheal intubation, as well as reduce the number of medications used for general anaesthesia and their side effectsMethod:We performed a randomized blind experiment on laparoscopiccholecystectomy (LC) patients in the General Surgery Department of TishreenUniversity Hospital in Lattakia between 2021-2022.The number of patients (40 patients) most of whom are between ASA1 and ASA2. We excluded patients with obesity, acute cholecystitis, history of abdominal surgery, also psychiatric patients, pregnant patients and patients with local analgesics as well as egg allergies.The ages of the patients are between 20-75 years.All patients went through LC while receiving local Lidocaine 2% through the layers of the skin at trocar sites, along with intravenous (IV) Ketofol.The procedure lasted 45-100 minutes that included initiation of sedation up until the patients' eyes open at the end of surgery .Conclusion :None of our patients in this study showed signs of discomfort under the mentioned pressure. No post-surgical complications were observedOut of 40 patients only one needed general anesthesia and five needed muscle relaxant (Atracurium 10 mg) which aided in the avoidance of general anesthesia , and that happened with consistent monitoring.Ketofol was noted to be safe for all patients and succeeded in providing hemodynamic stability during the surgery. We recommend using this method. Also we recommend further studies using the same Ketofol mixture .